Factors influencing the use of E-Wallet as a payment method among students in University Malaysia Kelantan (UMK) City Campus - Lim Sze Fang; Nur Anis Amirah Othman; Nurul Izzah Ahmad Supian; Siti Nur Aida Ali @Alimin (2023)
Nowadays, there are noticeable increase of cashless transactions due to development in financial technologies. As the result, there being expansion of fintech products such as e-wallet, that consumers are shifting from cash-based to the cashless. By today, young adult consumers in 21st century especially among students regarded as one of the tech-savvy because they were born in the era of the technologies. This study is aim to examine the factor influencing the use of e-wallet as a payment method among students in University Malaysia Kelantan City Campus by applying extended technology acceptance model (TAM). Total of 364 questionnaire were collected from the respondent of e-wallet among students in university Malaysia Kelantan City Campus. By applying one step approach for instance, measurement model reliability findings from this study reveal that perceived of use, privacy and security, social influence and speed with the intention in use of e-wallet. This study helps with the service providers of the digital marketplace further to have a better understanding for the usefulness of using this e-wallet for the transaction purposes.